2005
DOI: 10.1007/s10570-005-2177-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of 6-O-(4-stearyloxytrityl)Cellulose acetate Langmuir–Blodgett Films

Abstract: Multilayer films of 2,3-di-O-acetyl-6-O-(4-stearyloxytrityl)cellulose (ASTC) were prepared and investigated. The fairly high surface pressure (p)-area (A) isotherms (36-47 mN/m) suggest that the balky and hydrophobic trityl group contribute to form a condensed monolayer. The cellulose derivative formed a homogeneous monolayer at 10 mN/m. The monolayer on the water surface was transferred successfully at 10 mN/m onto various substrates by modifying the preparation methods, to form Z-type multilayer films. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In a previous paper, we made various attempts to prepare high-quality LB films of 6-O-(4-stearyloxtytrityl)cellulose and obtained multilayer Z-type films by the vertical dipping method. 26 Then, we tried to prepare a 6-O-stearylcellulose LB film by applying the improved method at a pressure π ) 10 mN m -1 at 20 °C. The 6-O-stearylcellulose monolayer was also transferred only by the upward stroke onto mica and was not transferred by the downward stroke, indicating that Z-type deposition occurred.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous paper, we made various attempts to prepare high-quality LB films of 6-O-(4-stearyloxtytrityl)cellulose and obtained multilayer Z-type films by the vertical dipping method. 26 Then, we tried to prepare a 6-O-stearylcellulose LB film by applying the improved method at a pressure π ) 10 mN m -1 at 20 °C. The 6-O-stearylcellulose monolayer was also transferred only by the upward stroke onto mica and was not transferred by the downward stroke, indicating that Z-type deposition occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of C 18 C LB films was applied to our improved method described in a previous report. 26 The vertical dipping method was used to deposit the surface monolayer onto the substrate. The upward and downward stroke rate is 10 and 7 mm min -1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study,26 we made various attempts to transfer a homogeneous STCAc monolayer by a vertical dipping method, and then multilayers could be prepared with a transfer ratio of unity. Thus, we attempted to prepare an STCFc LB film by the improved method, but trials of deposition failed.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous article,24, 25 we synthesized a series of novel 4‐alkoxytrityl chlorides with various chain lengths and succeeded in reacting cellulose with novel 4‐alkoxytritylation reagents with a high degree of substitution (DS) and high regioselectivity at the 6‐ O position. Moreover, the cellulose derivative formed a homogeneous monolayer at the air–water interface, and the monolayer was transferred successfully onto a substrate; this indicated that even the cellulose with the 6‐ O ‐mono‐alkyl substituent formed a stable LB film 26…”
Section: Introductionmentioning
confidence: 96%